Molecular characterisation of a new cassava geminivirus (ACMV-SA) in South Africa - Essiedu, Emmanuel K. O (My University, 1995)
Cassava (Mamhot esculenta Crantz) is a perennial woody shrub grown mainly in Latin America, Africa and Asia for its starchy tuberous roots. The cassava crop provides a lot of calories for both animal and human consumption as well as starch for industrial use. Because of its broad adaptability to a variety of soil and climatic conditions (such as drought tolerance and ability to grow on depleted and marginal soil), the crop is very important to the agroeconomy of several tropical countries. The main threat to the crop's survival is the Cassava Mosaic Disease (CMO) caused by the African Cassava Mosaic Virus (ACMV). This virus is a bipartite geminivirus. Recently a new strain of ACMV (i.e, ACMV-SA) has been observed to infect cassava crops in Kwazulu-Natal and Eastern Transvaal in South Africa. Initial studies of a 793bp Polymerase chain reaction (PCR) generated fragment sequence of the DNA-A component of the virus reveals that it shares a higher sequence homology with a monopartite TYLCV than with its other bipartite ACMV counterparts. This unique ACMV-strain is a cause for concel? which needs to be further investigated so that an effective approach can be taken to combat its devastating influence on cassava in South Africa. In this project further characterization of DNA-A of ACMV-SA was pursued so that: (1) antisense-Afll ORF (putative polymerase) expression could be developed in genetically engineered virus-resistant cassava; (2) the new virus could be compared with other similar geminiviruses. The characterization was done by: (1) Partially sequencing a 607bp ACI PCR-generated fragment of ACMV-SA cloned into Pstl siteof pBluescript SK(-) and comparing the sequence with ether geminiviruses; (2) constructing a restriction map of the DNA-A of ACMV-SA cloned into pBluescript KS so as to identify convenient restriction sites for future subcloning experiments. For the Agrobacterium transformation studies-jj; vitro plantlets, callus and suspension cell cultures for cassava an,.I tobacco were maintained. Protoplast isolation from cell suspension cultures was carried out for purposes of inoculating them with DNA-A of ACMV-SA. An attempt was made to clone the 607bp ACI fragment of ACMV-SA into the plant transformation vectors pBINl9 and pBI121.
A Thesis Submitted to the Faculty of Science University of the Witwatersrand, Johannesburg in Partial Fulfilment of the Requirements for the Degree of Master of Science. February 1995.